118k views
3 votes
Solve the following system of equations

-4x - 9y =24

7x + 3y =9

User Susaj S N
by
4.8k points

2 Answers

1 vote

Answer:

x = 3 and y = -4

Explanation:

It is given that,

-4x - 9y = 24 -----(1)

7x + 3y = 9 ---(2)

To find the solution of given equations

eq(2) * 3 ⇒

21x + 9y = 27 -----(3)

eq(1) + eq(3) ⇒

-4x - 9y = 24 -----(1)

21x + 9y = 27 -----(3)

17x = 51

x = 51/17 = 3

Substitute the value of x in eq(1)

-4x - 9y = 24 -----(1)

-4*3 - 9y = 24

-9y = 24 + 12

-9y = 36

y = 36/(-9) = -4

Therefore x = 3 and y = -4

User TinsukE
by
6.0k points
5 votes

Answer:

The solution is:


(3, -4)

Explanation:

We have the following equations


-4x - 9y =24


7x + 3y =9

To solve the system multiply by 3 the second equation and add it to the first equation


3*7x + 3*3y =3*9


21x + 9y =27


-4x - 9y =24

---------------------------------------


17x=51


x=(51)/(17)


x=3

Now substitute the value of x in any of the two equations and solve for y


7(3) + 3y =9


21 + 3y =9


3y =9-21


3y =-12


y =-(12)/(3)


y =-4

The solution is:


(3, -4)

User Krvkir
by
5.5k points